2008
DOI: 10.1111/j.1744-7348.2008.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of banana bunchy top virus infection on morphology and growth characteristics of banana

Abstract: Field experiments were conducted in Oahu, Hawaii, to investigate the effects of banana bunchy top virus (BBTV) infection on growth and morphology of banana (Musa acuminata). The time interval between aphid inoculation of BBTV and the initial appearance of disease symptoms (i.e. incubation period) was also determined. Plants infected with BBTV showed a significant reduction in petiole size (i.e. length and distance), plant canopy and height, leaf area, pseudostem diameter and chlorophyll content compared with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…J. Plant Pathol., 6 (2): 36-47, 2015 to stress physiology (Hooks et al, 2008). Chlorophyll a and b are the two most important pigments used in plant photosynthetic processes and low levels of these chlorophylls can directly limit photosynthetic activity (Taiz and Zeiger, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…J. Plant Pathol., 6 (2): 36-47, 2015 to stress physiology (Hooks et al, 2008). Chlorophyll a and b are the two most important pigments used in plant photosynthetic processes and low levels of these chlorophylls can directly limit photosynthetic activity (Taiz and Zeiger, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In Mungbean plants infected with Mungbena Yellow Mosaic Virus (MYMV), Sinha and Srivastava (2010) reported a reduction in chlorophyll at different stages of growth. Hooks et al (2008) also reported a reduction in chlorophyll content in banana infected with Banana bunchy top virus. In ash gourd, a decrease in chlorophyll content caused by Bottle gourd Mosaic Virus (BgMV), Watermelon Mosaic Virus-2 (WMV-2) and papaya ringspot virus (PRSV) have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Banana plants can only be infected from (1) infected plant material and (2) the banana aphid when carrying the virus [3]. When people give away young banana plants or suckers to others the BBTV can spread.…”
Section: Introductionmentioning
confidence: 99%
“…The wind can carry aphids many kilometres, which may result in further spreading the BBTV. Hook et al [3] showed that the incubation period of BBTV or appearance of symptoms in banana plants ranged from 25 to 85 days after aphid inoculation.…”
Section: Introductionmentioning
confidence: 99%